Effectiveness of mandibular advancement orthodontic appliances with maxillary expansion device in children with obstructive sleep apnea: a systematic review - Yue Sun; Yifan Jia; Shaotai Wang; Chengjing Xu; Yue Qu; Min Hu; Huan Jiang (BMC Oral Health, 2024)
Abstract Background The current review aims to explore the evidence regarding the effectiveness of mandibular advancement orthodontic appliances with maxillary expansion device in treating pediatric Obstructive Sleep Apnea (OSA). Materials and methods A systematic literature search was conducted across PubMed, Cochrane Central, Web of Science, Embase, Scopus databases, Chinese Biomedical Database, Chinese National Knowledge Infrastructure, and Wanfang. The research involved children and adolescents (under 16 years old) who received mandibular advancement and maxillary expansion functional orthopedic appliances for OSA treatment. We performed narrative reviews and subsequently amalgamated the findings from the studies. Results Six articles were included for review. Although a small number of studies were included, the research suggested the potential advantages of mandibular advancement for children with OSA. Following treatment, there was a decrease in AHI/RDI, an improvement in sleep quality, and the increase in oxygen saturation. Conclusions The limited quantity and quality of existing studies necessitate caution when drawing conclusions about the effectiveness of mandibular advancement and maxillary expansion for OSA. In the future, larger and well-designed randomized controlled trials (RCTs) are needed to provide more robust evidence. Patients should be carefully selected, and their orthodontic indications should be thoroughly evaluated before inclusion in such trials.We encourage researchers to design studies that monitor patients over several years to provide a comprehensive understanding of the long-term effectiveness. Trial registration This study was registered in PROSPERO(CRD42023480407) on November 20, 2023.